Analysis of inferior nasal turbinate width and concha bullosa in subjects with nasal septum deviation: a cone beam tomography study - Shishir Ram Shetty; Saad Wahby Al Bayatti; Natheer Hashim Al-Rawi; Hesham Marei; Sesha Reddy; Hossam Abdelatty Abdelmagyd; Sangeetha Narasimhan; Sausan Al Kawas; Asok Mathew (BMC, 2021)
Abstract Background In individuals with nasal septal deviation (NSD), compensatory hypertrophy of the nasal turbinates occurs as a protective mechanism of the nasal passage from dry and cold air. NSD associated nasal turbinate hypertrophy is usually recurrent, requiring repetitive imaging. Therefore, a multiplanar imaging modality with a low radiation dose is best suited for long-term follow-up of this condition. This study aimed to evaluate the association of width of inferior turbinates and presence of concha bullosa with the degree of NSD using Cone beam computed tomography (CT). Methods The CBCT scans of 100 patients with NSD were selected as per convenience sampling and were evaluated by two maxillofacial radiologists. The width of the non-hypertrophied inferior turbinate (NHT) on the convex side of the NSD, and hypertrophic inferior turbinates (HT) on the concave side of the NSD were measured at three locations. The septal deviation angle (SDA) and the presence of concha bullosa (CB) were determined. Results A significant difference was observed in the anterior, middle, posterior, and mean widths between HT and NHT (p < 0.001). There was a significant difference in the widths of the HT and NHT among different types of NSD. A strong positive correlation (r = 0.71, p < 0.001) was found between SDA and the mean width of the HT. Age (P = 0.71) and gender (P = 0.65) had no significant difference among different types of NSD. Regression analysis revealed that the presence of CB (p = 0.01) and middle width of the HT (p < 0.001) are significant predictors of SDA and type of NSD. Conclusion The results of the present study reveal that the middle width of the HT and the presence of CB influence the degree of NSD. The present study results recommend the use of CBCT as a substitutive low radiation dose imaging modality for evaluation of NSD, CB, and associated inferior turbinate hypertrophy.